PRODUCTION AND SENSORY EVALUATION OF JAM FROM BLENDS OF PINEAPPLE AND AVOCADO ENRICHED WITH HONEY FOR SUSTAINABLE HEALTH - Emeka Ebele Cynthia; Arubayi Diana O (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This main objective of this research work was to carry out the production and sensory evaluation of jam made from pineapple and avocado blended with 30%, 40% and 50% proportions of pineapple and enriched with honey for sustainable health. Fruits are rich in nutrients and can promote good health and wellbeing. Fruits are produced abundantly in their season such that if not well preserved, will result to a massive waste. Jam is one of such foods that can be produced for the purpose of reducing food wastage, increasing food value, income generation and product circulation in and out of season. The study sought answers to three research questions. The instrument used for data collection was a nine point hedonic scale which was as subjected to reliability testing. The test yielded a reliability coefficient of 0.718. Two fruits were used for jam production in this study (pineapple and avocado). Avocado is very low in sugar content and pectin. Therefore, to produce a well textured, sweetened and flavoured jam using this fruit, pectin ( from blends of pineapple), acid and a sweetener were added. After production, a sensory evaluation was carried out to ascertain the level of acceptability of the organoleptic attributes of taste, flavour, colour and texture of the products. Findings show that, pineapple is the most suitable for jam production as 100% pineapple jam (Sample B) has the best taste, flavour, colour and is more generally accepted than others. Avocado/pineapple jam blends (samples A, C, and D) were not rejected as sample A (avocado/pineapple jam 70:30%) has the best texture and the mean scores for other organoleptic attributes were above average. Based on the findings the researchers concluded that home made pineapple and avocado jam blends have good flavour, taste, colour, texture, acceptability and shelf life and recommend production and consumption of same for sustainable health.